2018
DOI: 10.1007/s00223-018-0441-1
|View full text |Cite
|
Sign up to set email alerts
|

Passive Coping Strategies Are Associated With More Impairment In Quality Of Life In Patients With Fibrous Dysplasia

Abstract: Impairments in quality of life (QoL) have been reported in patients with fibrous dysplasia (FD). Here, we examine coping strategies in FD and assess whether these coping strategies are associated with QoL and disease severity. Ninety-two patients (66% females) filled out the Utrecht Coping List (UCL), Short Form-36, and the Brief Pain Inventory (BPI). Coping strategies of patients with FD were compared with reference data from a random sample of Dutch women and patients with chronic pain. Compared to healthy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…On the one hand, physically active older people usually use active or problem-focused coping strategies [ 44 ] and also use more active strategies to cope with pain [ 26 ]. On the other hand, the use of passive and avoidant pain coping strategies negatively influences the physical role [ 30 ] that is related with a negative interpretation of pain situation [ 19 , 20 ], which could lead to a more negative interpretation of their own limitations to day-to-day activities, or their physical role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, physically active older people usually use active or problem-focused coping strategies [ 44 ] and also use more active strategies to cope with pain [ 26 ]. On the other hand, the use of passive and avoidant pain coping strategies negatively influences the physical role [ 30 ] that is related with a negative interpretation of pain situation [ 19 , 20 ], which could lead to a more negative interpretation of their own limitations to day-to-day activities, or their physical role.…”
Section: Discussionmentioning
confidence: 99%
“…Catastrophizing during old age is related with depressive symptoms, which in turn affects older adults' HRQoL, functional impairment, and chronic illness [ 28 , 29 ]. For instance, it has been found that the use of passive strategies negatively affects physical role [ 30 ]. In addition, physical role, which is related to better mobility, a high rate of PA, and daily life activities performance, contributes to diminishing catastrophizing [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“… 25 26 Contrarily, individuals who use more passive coping styles tend to doubt their abilities and have worse mental health, therefore lowering their quality of life. 27 According to the transactional model of stress and coping proposed by Lazarus and Folkman in 1984, 28 an individual’s reaction to a stressful event is mediated by their subjective evaluation (ie, appraisal) of the environment and their process of coping with the event. Appraisals of situations and coping behaviour are influenced by characteristics such as personality, competence and social skills.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, structured coping frameworks are often used in pain literature to elucidate important outcomes such as functioning and quality of life (Rotman et al., 2018). Such frameworks typically categorize coping mechanisms as primary, secondary, or passive.…”
Section: Introductionmentioning
confidence: 99%